Optimalisasi Pengelolaan Zakat Profesi: Analisis Problematika dan Strategi Penanganannya di BAZNAS Jombang - Amin Awal Amarudin; Nurun Nisaul Khusna (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
Professional zakat holds significant potential for the welfare of mustahik (beneficiaries) but faces various operational challenges requiring intervention. This study aims to analyze management strategies, identify problems, and formulate solutions for professional zakat management at BAZNAS Jombang. Utilizing a qualitative approach based on POAC (Planning, Organizing, Actuating, and Controlling) management functions, data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman model. The findings demonstrate: 1). BAZNAS Jombang effectively applies POAC principles. Management involves structured planning 2–3 months in advance, focusing on collections from civil servants (ASN) and the public, with distribution targeting health, education, and social assistance via surveys. Organization is digitalized through department treasurers without a dedicated internal structure. Implementation utilizes payroll deductions and bank transfers, alongside collaborations with government and social agencies. Oversight includes quarterly internal and annual external audits, with published reports ensuring transparency. 2). Identified problems include incomplete ASN participation, limited human resources, low literacy among non-ASN donors, a lack of mandatory regional regulations, trust issues, fraudulent beneficiary claims, and courier-dependent financial reporting. 3). Mitigation strategies involve weekly coordination meetings, social media use for transparency, educational events, strengthened distribution, involvement of religious leaders, advocating for mandatory regulations, establishing a verification forum, and optimizing report delivery. The research suggests that future studies adopt comparative or mixed-method approaches across various zakat institutions to provide more comprehensive insights into professional zakat management.